Comparative Analysis of the Influence of Systematic Risk, Idiosyncratic Risk, and Investor Sentiment on Stock Returns in Banking Companies Listed on the Indonesia Stock Exchange and the Malaysia Exchange - Deby Dewanty Daulay; Khaira Amalia Fachrudin; Amlys Syahputra Silalahi (Indonesian Journal Publisher, 2025)
Stock returns serve as key indicators reflecting investment performance and become the primary focus of investors in capital market decision-making, with the banking sector playing a strategic role in driving economic growth in Indonesia and Malaysia. This study aimed to analyze the impact of systematic risk, idiosyncratic risk, and investor sentiment on banking stock returns in the Indonesia Stock Exchange (BEI) and Bursa Malaysia. Employing a quantitative approach with explanatory research and comparative methods, the study examined 21 companies from BEI and 7 companies from Bursa Malaysia during 2020-2023. Through panel data analysis using EViews, findings revealed that in BEI, systematic risk significantly negatively influences stock returns by 10.74% (p-value 0.001), idiosyncratic risk shows a highly significant positive impact of 594.00% (p-value 0.000), while investor sentiment has no significant effect (p-value 0.331). In Bursa Malaysia, systematic risk significantly negatively affects stock returns by 14,11%% (p-value 0,0028), idiosyncratic risk shows a significant negative impact of 116,065% (p-value 0,0803), and investor sentiment significantly positively influences returns by 0,57% (p-value 0,0001). The research model explains 59.41% of stock return variations in BEI and 20.63% in Bursa Malaysia. Comparative analysis reveals no significant difference in systematic risk between the two exchanges and consistent combined data, but there are significant differences in idiosyncratic risk and investor sentiment which are inconsistent with the significance results of Bursa Malaysia with BEI and the combined data of the two exchanges.